The effect of the molecular weight of blackberry polysaccharides on gut microbiota modulation and hypoglycemic effect in vivo - Xi, Lai; Weibing, Xu; Shuyong, Fu; Sheng-Hua, Li; Xiong, Fu; Chin-Ping, Tan; Ping-Ping, Wang; Zu-Man, Dou; Chun, Chen (Royal Society of Chemistry, 2024)
Blackberry polysaccharides with certain molecular weight distribution have good bioactivity. In this research, type 2 diabetes mice were used to investigate the hypoglycemic effect of blackberry polysaccharides with three different molecular weights, BBP (603.59 kDa), BBP-8 (408.13 kDa) and BBP-24 (247.62 kDa), through gut microbiota modulation. Blackberry polysaccharides exhibited stronger hypoglycemic activity after degradation, and the FBG of BBP, BBP-8 and BBP-24 was reduced to 20.21 ± 4.17 mmol L−1, 20.6 ± 7.23 mmol L−1 and 17.32 ± 6.59 mmol L−1 and OGTT-AUC was reduced by 14.76%, 19.80% and 25.04%, respectively, after 8-week intervention. Furthermore, 16S rRNA gene sequencing analysis indicated that BBP, BBP-8 and BBP-24 could reshape the diversity and composition of the gut microbiota. From 0 to 4 weeks, the F/B of BBP, BBP-8 and BBP-24 reduced by 56.44%, 47.19% and 62.04%, reaching 3.39, 6.54, and 3.11 in the 8th week, respectively, which suggested the faster utilization of BBP-24. Moreover, the intervention the three blackberry polysaccharides increased the relative abundance of the targeted beneficial bacteria Oscillospira and Bacteroidaceae Bacteroides and decreased the relative abundance of the pathogenic bacterium Allobaculum. In general, the result demonstrated that blackberry polysaccharides with a lower molecular weight are more easily fermented, making the theoretical basis for the development of blackberry polysaccharides as a probiotic food to rapidly regulate intestinal flora for type 2 diabetes.